2019
DOI: 10.1016/j.marchem.2019.103669
|View full text |Cite
|
Sign up to set email alerts
|

Quantification, extractability and stability of dissolved domoic acid within marine dissolved organic matter

Abstract: The widespread diatom Pseudo-nitzschia can produce domoic acid (DA). DA is a compound with well described neurotoxic effects on vertebrates including humans known as amnesic shellfish poisoning (ASP) syndrome. It has also been suggested to serve as an organic ligand that binds to iron and copper. By binding these trace elements, DA may increase their solubility and bioavailability. In order to serve this function, DA has to be excreted and reabsorbed by the cells. Only few records of dissolved domoic acid (dDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 96 publications
(175 reference statements)
1
6
0
Order By: Relevance
“…The current study is consistent with a large-scale study in the transect of the east Atlantic Ocean, detecting dissolved DA in the Southern Ocean [ 29 ]. The highest dissolved DA concentration was found around the equator; dissolved DA was detectable in all surface water samples as south as 70° S [ 29 ]. This knowledge adds to the pivotal importance of studying DA presence and impact in global as well as Antactic ecosystems.…”
Section: Discussionsupporting
confidence: 92%
“…The current study is consistent with a large-scale study in the transect of the east Atlantic Ocean, detecting dissolved DA in the Southern Ocean [ 29 ]. The highest dissolved DA concentration was found around the equator; dissolved DA was detectable in all surface water samples as south as 70° S [ 29 ]. This knowledge adds to the pivotal importance of studying DA presence and impact in global as well as Antactic ecosystems.…”
Section: Discussionsupporting
confidence: 92%
“…Since chromatograms of DOM represent unresolved humps, the abundance of single analytes cannot easily be deduced. 13,18 Instead, complex mass spectra in broadly eluting fractions must be analysed. However, the visual analysis of raw data is overburdened by the large number of spectra, and statistical analyses capable of extracting information from direct infusion datasets (such as principal component analysis) require unfolding of the multidimensional data.…”
Section: Introductionmentioning
confidence: 99%
“…A search for DA biosynthesis transcripts (Brunson et al 2018) did not yield strong evidence for expression of the DA biosynthesis gene cluster in this experiment (Table S1; Table S2). However, a few studies have reported DA production in the SO (Silver et al 2010; Geuer et al 2019), but the temporal, spatial and environmental factors that elicit DA production remain unclear. Further work is required to investigate whether resident Pseudo-nitzschia can produce the toxin under conditions not examined in our study, or if DA producing Pseudo-nitzschia are likely to migrate into a warmer SO.…”
Section: Resultsmentioning
confidence: 99%